2016
DOI: 10.1089/neu.2015.4261
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cranioplasty on Cerebral Hemodynamics as Measured by Perfusion Computed Tomography and Doppler Ultrasonography

Abstract: Cranioplasties are performed to protect the brain and correct cosmetic defects, but there is growing evidence that this procedure may result in neurological improvement. We prospectively studied cranioplasties performed at our hospital over a 5-year period. The National Institute of Health Stroke Scale and Barthel index were recorded prior to and within 72 h after the cranioplasty. A perfusion computed tomography (PCT) and transcranial Doppler sonography (TCDS) were performed prior to and 72 h after the surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Once the brain swelling has subsided, the surgical skull defect must be bridged [4]. In the past, the use of autologous calvarial bone (ACB) was considered the gold standard for secondary cranioplasty (CP).…”
Section: Introductionmentioning
confidence: 99%
“…Once the brain swelling has subsided, the surgical skull defect must be bridged [4]. In the past, the use of autologous calvarial bone (ACB) was considered the gold standard for secondary cranioplasty (CP).…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the utility of the MCA PI for assessment of cerebral hemodynamics, we drew probability charts of the associations between the ipsilateral MCA PI and ICP and CPP for ICPs exceeding 20, 25, and 30 mm Hg and CPPs lower than than 70, 60, and 50 mm Hg by various MCA PI values. Although the optimal CPP of neurocritical patients remains unclear, CPPs lower than 50 mm Hg should be avoided . As the charts show, an extremely high MCA PI indicated a dangerous ICP elevation or CPP reduction.…”
Section: Discussionmentioning
confidence: 89%
“…For example, one animal experiment revealed a 2‐way correlation between the PI and CVR under different conditions . Moreover, we had little knowledge about the effect of craniectomy (rather than a craniectomy‐induced ICP reduction) or cranioplasty on the MCA PI, and the surgery (craniectomy or cranioplasty) may alter cerebral hemodynamics . Additionally, we found no significant correlation between the MCA PI and the CPP ( P > .05), and the MCA PI poorly predicted the CPP (AUC <0.75).…”
Section: Discussionmentioning
confidence: 99%
“…The CP-associated complication rates between early (< 3 months), and late (> 6 months) CP was significantly higher among patients undergoing late CP. 37 Chaturvedi et al (2016) studied and analyzed complications following CP after DC, retrospectively, and found that mortality rate was 1.35% and overall complication rate 31%. 38 In the study of Andrabi et al (2017), complications were noted in 15.25% (n = 36) of the patients; wound infection/dehiscence 6.78% (n = 16) was the most common complication encountered.…”
Section: Discussionmentioning
confidence: 99%